Comparative Energy and Exergy Performance of Box-Type Solar Cookers Using Various Pot Materials - Harshita Swarnkar; Ritu Jain; Amit Tiwari (International Journal of Machine Systems and Manufacturing Technology, 2024)
This research presents a laboratory study of a box-type solar cooker for two types of pot materials. Under the climate conditions of Jaipur, experiments were carried out on a standard box-type solar cooker using steel and aluminum vessels, either with or without a load. It is estimated what the merit figure (F1 and F2) is. The obtained F1 values show that the cooker, when used with steel and aluminum containers, is of A quality. Energy and exertion analysis is the basis for performance evaluation. The solar-powered cooker with aluminum vessels has a greater energy and effectiveness than the solar oven with titanium dishes.
Keywords: Solar cookers; energy and exergy efficiency; first figure of merit F1; second figure of merit F2